Sistematik Literatur Pengaruh Model Pembelajaran Project Based Learning Berbasis Literasi Terhadap Keterampilan Berpikir Kreatif Siswa - Perawati Bte Abustang; Jusmawati Jusmawati; Fitriani Fitriani; Hesti Meliana; Ahmad Jais Banyal; Kurniawati Buton (Journal on Education, 2024)
The project-based learning model (PJBL) uses projects/activities as goals. Project Based Learning (PjBL) focuses on student activities in the form of collecting information and using that information to create something that is useful for the lives of the students themselves and others. The PjBL Learning (Project Based Learning) model is designed in such a way that students can solve a problem through project activities. The aim of this research is to determine the effect of the literacy-based project based learning model on students' creative thinking abilities. The author looked for several relevant sources on Google Scholar and other sources. The researcher applied a systematic literature review method. The main research method of the articles reviewed was quantitative. Based on research results, the project based learning model is very suitable to be applied in the classroom learning process to improve students' creative thinking skills. Because the project based learning model focuses on creating projects as the main learning activity, this will improve creative thinking skills because students will be more freedom in creating or designing a project. And learning experiences can help them improve their creative.